Kaleidofin - Mendonca, Valerie; Sharma, Supriya (London : Indian Institute of Management, Ahmedabad, 2022)
Puneet Gupta and Sucharita Mukherjee were the former chief financial officer and chief executive officer of the Institute for Financial Management and Research Holdings Pvt. Ltd, respectively. They had considerable experience in the Indian financial inclusion domain and co-founded Kaleidofin in 2017. Kaleidofin offered goal-based savings and investment products to the underserved segments by 'propelling people towards life goals by providing them with customised financial solutions'. The co-founders had observed that low- and middle-income groups had no access to mainstream financial services. Volatile and irregular incomes, low technology adoption, and a thin line of credit characterised customers in this segment. Financial institutions steered clear of servicing these customers because of high distribution and servicing costs, and customers were unaware of financial products and services. Kaleidofin aimed at servicing this segment by offering them a customised financial product including flexible investments and access to credit and insurance.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Corporations -- Finance